2022
DOI: 10.3389/fnagi.2022.825086
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Neuroinflammation: Crucial Pathological Mechanisms in Traumatic Brain Injury-Induced Neurodegeneration

Abstract: Traumatic brain injury (TBI) is one of the most common diseases in the central nervous system (CNS) with high mortality and morbidity. Patients with TBI usually suffer many sequelae in the life time post injury, including neurodegenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). However, the pathological mechanisms connecting these two processes have not yet been fully elucidated. It is important to further investigate the pathophysiological mechanisms underlying TBI and TBI-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 189 publications
1
51
0
Order By: Relevance
“…Finally, Fritsch et al found greater gene expression of cGAS and STING in microglia compared to other brain cells, suggesting that microglia may be central to cGAS-STING activation (Supplementary Figure 5, Fritsch et al, 2022 ), which is an important observation consistent with the central role of microglia in neuroinflammation (Shao et al, 2022 ). However, others have also shown that astrocytes are involved in TBI-related responses (Burda et al, 2016 ; Michinaga and Koyama, 2021 ) and cGAS-STING activation (Jeffries and Marriott, 2017 ), and the current data do not rule out the contribution of other glial cells—especially since cell isolation protocols themselves can contribute to inflammatory microglial activation (Cadiz et al, 2022 ) and the authors did not report on cGAS-STING levels in adherent cells other than microglia.…”
mentioning
confidence: 58%
“…Finally, Fritsch et al found greater gene expression of cGAS and STING in microglia compared to other brain cells, suggesting that microglia may be central to cGAS-STING activation (Supplementary Figure 5, Fritsch et al, 2022 ), which is an important observation consistent with the central role of microglia in neuroinflammation (Shao et al, 2022 ). However, others have also shown that astrocytes are involved in TBI-related responses (Burda et al, 2016 ; Michinaga and Koyama, 2021 ) and cGAS-STING activation (Jeffries and Marriott, 2017 ), and the current data do not rule out the contribution of other glial cells—especially since cell isolation protocols themselves can contribute to inflammatory microglial activation (Cadiz et al, 2022 ) and the authors did not report on cGAS-STING levels in adherent cells other than microglia.…”
mentioning
confidence: 58%
“…Moreover, microglial cells provide immune responses in respond to a number of stimuli ( 22 ). After TBI, microglia are activated, the activated microglia secrete a large number of neuroimmune inflammatory factors such as interleukin-1β (IL-1β), IL-10 and tumor necrosis factor-α (TNF-α), thus exacerbating the inflammatory response and leading to a series of brain injuries, including cognitive impairment, blood-brain barrier (BBB) disruption and brain edema ( 23 , 24 ). Recently, Eps15, the parent gene of circRNA EPS15, has also been suggested to regulate microglial cell activation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A promising biomarker that is not as widely employed for tau is the inflammatory marker triggering receptor expressed on myeloid cells 2 (TREM2), a triggering receptor found in several myeloid lineage cells such as peripheral macrophages, dendritic cells and microglial cells in the central nervous system (CNS) [101] . TREM2 is also expressed in the microglia of the brain, regulating microglial activation and playing a multi-faceted role in its immune response [102] , [103] .…”
Section: Fluid Biomarkersmentioning
confidence: 99%